Association of age-related macular degeneration on fracture risks among osteoporosis population: a nationwide population-based cohort study - Bing-Yu Chen; Chi Chin Sun; Ting-Shuo Huang; Tsai-Sheng Fu; Chia-Yi Lee; Fang-Ping Chen (BMJ Open)
Objectives Visual impairment is an important risk factor for fracture in the elderly population. Age-related macular degeneration (AMD) is the leading cause of irreversible visual impairment in elderly people. This study was conducted to explore the relationship between AMD and incident fractures in patients with osteoporosis (OS).Design Retrospective analysis of Taiwan’s National Health Insurance Research Database (NHIRD).Setting A multicenter study conducted in Taiwan.Participants and controls The current study used the NHIRD in Taiwan between 1996 and 2011. A total of 13 584 and 54 336 patients with OS were enrolled in the AMD group and the non-AMD group, respectively.Intervention Patients with OS were included from the Taiwan’s NHIRD after exclusion, and each patient with AMD was matched for age, sex and comorbidities to four patients with non-AMD OS, who served as the control group. A Cox proportional hazard model was used for the multivariable analysis.Primary outcome measures Transitions for OS to spine fracture, OS to hip fracture, OS to humero-radio-ulnar fracture and OS to death.Results The risks of spine and hip fractures were significantly higher in the AMD group (HR=1.09, 95% CI=1.04 to 1.15, p<0.001; HR=1.18; 95% CI=1.08 to 1.30, p=0.001, respectively) than in the non-AMD group. The incidence of humero-radio-ulnar fracture between AMD and non-AMD individuals was similar (HR=0.98; 95% CI=0.90 to 1.06; p=0.599). However, the risk of death was higher in patients with OS with older age, male sex and all types of comorbidity (p<0.05), except for hyperthyroidism (p=0.200).Conclusion Patients with OS with AMD had a greater risk of spine and hip fractures than did patients without AMD.